1992
DOI: 10.1002/stem.5530100604
|View full text |Cite
|
Sign up to set email alerts
|

Serum erythropoietin titers in hematological malignancies and related diseases

Abstract: Serum erythropoietin (Epo) titers in patients with various hematological malignancies and related diseases were determined by radioimmunoassay. Serum Epo titer was inversely correlated with hemoglobin concentration in iron deficiency anemia, aplastic anemia, myelodysplastic syndromes (MDS), acute leukemia, malignant lymphoma, multiple myeloma and myelofibrosis, but there was no correlation between serum Epo titer and hemoglobin concentration in chronic myelogenous leukemia or polycythemias. Serum Epo titers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…Similar results were also obtained in studies abroad, although the EPO levels increased up to~100 mIU/mL in some patients with stage 3 CKD [5,6]. In contrast, EPO levels were >50 mIU/mL in most patients with hematological diseases [3,4].…”
Section: Rationalesupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were also obtained in studies abroad, although the EPO levels increased up to~100 mIU/mL in some patients with stage 3 CKD [5,6]. In contrast, EPO levels were >50 mIU/mL in most patients with hematological diseases [3,4].…”
Section: Rationalesupporting
confidence: 87%
“…In these reports, most patients with hematopoietic disorders such as aplastic anemia and myelodysplastic syndromes (MDS) with Hb levels of <10 g/dL showed serum EPO levels of >50 mIU/ mL [by radioimmunoassay or the chemiluminescent enzyme immunoassay (CLEIA)] [3,4], whereas most CKD patients showed serum EPO levels of <50 mIU/mL [by enzyme-linked immunosorbent assay (ELISA) or the CLEIA method] [5,6] (different measurement methods may affect the measured value of EPO, but such an effect has not been examined). Moreover, it has been reported that the increase in EPO level in response to the decrease in Hb level is suppressed at more advanced stages of CKD [6].…”
Section: )mentioning
confidence: 99%
“…In agreement with pre vious studies [4][5][6][7], we found a significant inverse correla tion between the log Epo concentration and haematocrit in patients with acquired AA. Plasma Epo concentrations were much higher in patients with acquired AA than in patients with anaemia of other aetiologies.…”
Section: Discussionsupporting
confidence: 92%
“…Recombinant human Epo has been used as replace ment therapy in patients with impaired production of Epo and as a pharmacologic agent in patients with normal, but insufficient, Epo production [3]. Previous studies have shown that serum Epo concentrations are significantly higher in patients with AA than in normal controls and correlate inversely with haemoglobin concentrations [4][5][6][7], Because plasma Epo concentrations vary considerably among patients with the same haemoglobin concentra tion, we evaluated factors that may influence the Epo con centration in patients with acquired AA. Another aim of the present study was to provide information about the likelihood that patients with acquired AA might benefit from treatment with exogenous Epo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that, for similar degrees of anemia, patients with aplastic erythroid marrow had higher serum Epo levels than patients with iron deficiency anemia, and even more so compared to patients with megaloblastic anemia or thalassemia intermedia. [18][19][20] It has also been shown that serum Epo levels decreased rapidly on introduction of iron or vitamin B 12 for the treatment of iron deficiency 20 or megaloblastic anemia 20,21 well before any detectable change in hemoglobin. Similarly, we have observed that the kinetics of change of serum Epo levels after autologous hematopoietic stem cell transplantation was clearly dependent on the speed of erythroid engraftment.…”
Section: Discussionmentioning
confidence: 99%